Body fluid status in patients with pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension. (3rd October 2022) - Yogeswaran, A; Husain-Seyed, F; Tello, K; Sommer, N; Rako, Z A; Ghofrani, H A; Seeger, W; Richter, M J; Gall, H
Abstract: Introduction: Body fluid status can be determined by plasma volume status and extracellular water to total body water (ECW/TBW) ratio and is a well-known parameter associated with survival in patients with chronic heart failure (1–3). However, its prognostic impact in patients with pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) is not fully understood. Methods: 409 patients with PAH and CTEPH who entered the Giessen PH registry were included in this study (4). Plasma volume status was estimated using Duarte formula (ePVS = (1 − hematocrit) / hemoglobin × 100). ECW was calculated via Peters formula ((−2.47 × 0.842 + 8.76 × body surface area) for men and (−1.96 × 0.572 + 8.05 × body surface area) for women) and TBW via Watson formula ((2.447 − [0.09516 × age] + [0.1073 × height] + [0.3362 × body weight]) for men and (−2.097 + [0.1069 × height] + [0.2466 × body weight]) for women). Statistical analyzes were performed with R (The R Foundation). Results: Median age of the included patients was 65 [53, 74] years. Median ePVS and ECW/TBW ratio were 4.5 [3.9, 5.5] and 0.39 [0.37, 0.40]. Correlation analyses revealed that ePVS correlates with pulmonary artery wedge pressure (PAWP), pulmonary vascular resistance (PVR), cardiac index, and mixed venous oxygen saturation (SvO2), whereas ECW/TBW ratio did not correlate with pulmonary hemodynamics. Accordingly, univariate Cox regression revealed that ePVS but not ECW/TBW ratio was associated with mortality (HR: 1.18 [1.02, 1.37]). ePVS remained as an independent prognostic parameter in multivariate Cox regression analysis. Patients with high ePVS showed significantly decreased survival rates (log-rank p<0.001). Conclusion: ePVS but not ECW/TBW ratio is associated with prognostic parameters such as PVR, cardiac index and SvO2. Thus, ePVS may be an independent prognostic parameter in patients with PAH and CTEPH. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Deutsche Forschungsgemeinschaft (DFG, German Research Foundation)